Tales of the Fish Patrol. - London, Jack (Floating Press, 1906)
Take a voyage through the Pacific in this series of tales from Jack London, one of the foremost chroniclers of the American West. Set in a variety of locales in, around, and off the coast of San Francisco, the short stories and sketches collected in this volume are sure to please fans of fast-paced outdoor adventures, California culture, and travel writing.